The association between smoking status and tobacco outlets density and proximity: A cross-sectional study with geographical data from CHILILAB, 2016 - Le Tu, Hoang; Hoang Van, Minh (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objective: Smoking behavior among adults still exists in Vietnam. This paper aims to describe smoking behavior among people aged 15 and above, specifically those monitored by the demographic surveillance system – CHILILAB, in order to determine the association between smoking behavior and the tobacco outlets density and proximity. Methods: A cross-sectional study was conducted with a total of 5,076 households, with one 15-and-over member in each household selected randomly to answer the questionnaire. Coordinate data of households and tobacco outlets was collected. Smoking status was the main dependent variable. Distance from household to nearest tobacco outlet, and number of tobacco outlets in different radius were calculated using ArcGIS 10.4.1. Results: The prevalence of current smoking status was 17.1% (36.6% among male and 1.0% among female). The average distance to nearest tobacco outlet was 170.7 meters and an average of 3.1 tobacco outlets in radius of 100 – 200 meters around participants’ households. Both density and proximity of tobacco outlets showed associations with smoking prevalence. To reduce smoking prevalence among community, policymakers should consider applying a range of no-tobacco-outlet, as well as reduce the number of existed tobacco retailers. Conclusion: The density and proximity of tobacco outlets should be considered an important factor to be controlled in analysis related to tobacco smoking.